Propagação e conservação in vitro de acessos de jenipapeiro - Almeida, Camila Santos (2013)
The jenipapeiro (Genipa americana L.) has great economic importance both for its forest essence, as the production of food. Obtaining protocols is important for conservation of genetic resources conservation. The objectives of this study was to establish protocols for in vitro conservation jenipapeiro, and studies of the effect of different culture media on in vitro germination of seeds of this species and the effects of different culture media on the induction of somatic embryogenesis from explants of this culture. The experiments were conducted in the laboratory of Plant Tissue Culture Embrapa Coastal Tablelands, SE. To study the in vitro conservation of plant seeds were used arrays jenipapeiro from Cruz das Almas, Bahia; access Oiteiros, Sergipe and access Siriri, Sergipe. In the experiment of conservation tested different concentrations of mannitol - Test 1; ABA- Test 2, and variations of the MS and sucrose- test 3. After 150 days, the seedlings from the means of conservation, targeted and were inoculated on regeneration medium (MS gelled supplemented with 30 g L-1 sucrose, BAP (0 and 1 mg L-1) and 4,5 g L-1 Phytagel ®). For the germination experiment tested distilled water and different variations of MS salts and sucrose. For the experiment of somatic embryogenesis, seedling 90 days in vitro culture were segmented and transferred to a new MS medium supplemented with 30 g L-1 sucrose and different concentrations of 2,4 - 2,4-D-Dichlorofenoxyacetic (0 , 4 and 8 mg L-1) combined with concentrations of four-benzylaminopurine (BAP 0, 1, 2 and 3 mg L-1). In the stage of conservation, mannitol concentrations studied did not promote growth slowdown seedlings jenipapeiro, while, abscisic acid caused a reduction in the number of leaves. The means MS and ½ MS salt concentration in the presence of 30 g L-1 sucrose promoted slowing the growth of seedlings jenipapeiro can be recommended protocols for conservation by slow growth. The explants from the storage medium containing mannitol and maintained abscisic acid in the presence of 1,0 mg L-1 BAP phase of resumption showed higher morphogenetic response. Explants kept in storage phase in the presence of MS medium + 30 g L-1 sucrose and ½ MS 15 or 30 g L-1 sucrose, had lower morphogenetic response in the absence of BAP compared with the other treatments. In the stage of germination in vitro, it was observed that in the absence of salts and sucrose was highest percentage of normal seedlings and lowest shoot length. In the stage of somatic embryogenesis, the presence of 2,4-D, promoted greater percentage of explants with morphogenetic response. The shoot segments promoted greater response than the foliar concentration in the absence and 4 mg L-1 2,4-D. Furthermore, the presence of BAP induced reduced response to this variable stem explants and greater response to foliar explants.